O processo da tomada de decisão de compra a prazo: o efeito das diferenças individuais, do tipo de produto e das condições de pagamento - Mette, Frederike Monika Budiner (Universidade do Vale do Rio dos Sinos, 2016)
This thesis aimed to conduct a research on the individual decision-making that occurs in the credit purchase context, from theories and studies of economic psychology and consumer behavior. It was intended to analyze the effect of the product type and payment conditions in the credit purchase intention, as well as the influence of individual differences in this relationship. It was used an experimental methodology with three experiments in order to test the hypotheses from a theoretical model. In Experiment 1, with 8 experimental groups and a sample of 279 people, it was identified that there is a effect on the credit purchase propensity when there is a discount for cash payment, regardless of the interest rates. If there is no discount, the lower tends to be the credit purchase propensity i as there are no interest charges in the payments. Furthermore, it was concluded that individuals with high levels of materialism and impulsivity tend to buy more than those who have a high financial literacy. For Experiment 2, with 8 experimental groups and 314 respondents, the data collection was similar to the first, changing just the manipulations. As implication, it was found results that if there was no discount the lower tends to be the term purchase propensity, in the same way that the first one. By the way, it was proven the that the produt type influenced in the credit payment. In the Experiment 3, it was sought to verify only the effects related to the type of products, with 4 experimental groups for both products, and a sample of 171 people. It was found a crossed product interaction effect when the type of product is hedonic, so there were greater variations in the average of credit purchase intentionwhen the product was utilitarian. It was also proven that the utilitarian product has a higher forward purchase intention, so the bigger the effect that was noticed by the product variation.
Keywords: Tomada de decisão; Compra a prazo; Tipo de produto; Condições de pagamento; Diferenças individuais; Psicologia econômica; Decision-making; Credit purchase; Product type; Terms of payment; Individual differences; Economic psychology; ACCNPQ::Ciências Sociais Aplicadas::Administração